A high frequency of peripheral blood NKG2D+NK and NKT cells in euthyroid patients with new onset hashimoto's thyroiditis—a pilot study. (May 2014) - Guo, Hui; Xu, Bingchuan; Yang, Xige; Wang, Ye; Liu, Xiaobo; Cui, Chengri; Jiang, Yanfang
<x xml:space="preserve">Abstract</x> Hashimoto's thyroiditis (HT) is a T cell-mediated autoimmune disease. However, little is known about the role of different subsets of natural killer (NK) and natural killer T (NKT) cells at the early stage of the HT process. A total of 45 euthyroid patients with new onset HT and 40 age/gender-matched healthy controls (HC) were examined for the frequency of different subsets of NK and NKT cells and their function by flow cytometry. In comparison with that in HC, significantly higher percentages of peripheral blood CD3-CD56+ NK, NKG2D+, NKp30+ NK and NKT cells, but significantly lower percentages of NKG2A+, KIR2DL3+ inhibitory NK and NKT cells were detected in the HT patients. Furthermore, the percentages of NKG2D+ NK cells were correlated positively with the concentrations of serum anti-thyroid peroxidase antibody (TPOAb) in the HT patients. Moreover, the percentages of inducible IFN-γ and CD107a+ NK cells in the HT patients were significantly higher than those in HC. Our data suggest that activated NK cells may participate in the early pathogenic process of HT.